The improvement of students' assertive behavior through elaboration likelihood model - Tubigon, Aime D. (Animo Repository, 1996)
This study tests whether the level of assertive behavior of students increases after exposure to the Elaboration Likelihood Model (ELM) training program.Random selection was performed among the first year college students assigned to the control group who were not exposed to ELM program and experimental group who were exposed to ELM training program. The 20 participants were students enrolled at Brokenshire College for SY 1995-1996. All were freshmen college students. The participants were found to be slightly, quite, extremely and more than extremely non-assertive through the Rathus Assertiveness Scale. The experimental method of research used in this study was a pre-test posttest control group design wherein the control and experimental groups were tested before and after treatment.The control and experimental groups were given a simultaneous 3-day live-in training. The control group was exposed to a typical assertiveness training program while the experimental group was exposed to an ELM-based assertiveness training program. The effect of the ELM-based assertiveness training program was based on the difference in the level of assertiveness before and after exposure to the training program. The present study found out that: 1. Participants of the training program were non-assertive and majority of them were extremely non-assertive. 2. There was a significant difference in the level of assertiveness before and after exposure to the ELM training program. 3. There was no significant difference in the level of assertiveness before and after exposure of a typical assertiveness training program. 4. There was no significant difference in the level of assertiveness before exposure of the training program between control and experimental group. 5. There was a significant difference in the level of assertiveness between control and experimental groups after exposure to the training program. Experimental group significantly improved their level of assertiveness. 6. Both experimental and control group participants were motivated and expressed favorable thought regarding assertiveness after the training program. It was concluded, on the basis of the data gathered that: 1. First year college students of Brokenshire College were non-assertive. 2. ELM-based assertiveness training bring more improvement of assertive behavior than a typical assertiveness training.